Relationship Management and Fireflies Conservation in Klias and Weston, Beaufort, Sabah - Siti Rozziana binti Jeperi; Mahadimenakbar M. Dawood; Fiffy Hanisdah Saikim (IOP Publishing, 2020)
Fireflies from the genus Pteroptyx have drawn a lot of attention from humans due to their congregating behaviour and provided local communities with lucrative business opportunity. However, it is believed that the adjacent communities pose a threat of encroachment to the Klias and Weston – the hotspots for fireflies’ population mangrove ecosystem. Relationship Management has strategies and tactics to engage in sentiments, emotions, and then provide the best remedies. It has strategic power to connect hosts and guests as it emphasizes on ''give back and take away tourism” through incorporating guest-hosts both in the process of conservation and utilization of various resources and skills available to them. Our study has tried to find out the economic importance (use value) of the fireflies and culture for the benefits of fireflies, nature, environment, and local communities of the area where they exist in the real habitat situation. The study attempts to provide solution of the critical problems and situations that have been created by human beings for a long time for the sake of feeding our ego and gaining dominancy (temporary value) in their areas because of unethical education and lack of awareness about socio-economic benefits through current ecotourism developments. The highlighted significance of Relationship Management in fireflies’ conservation and ecotourism development may help in tackling the conflicts between human and fireflies, human and human, as well as in fireflies watching activities. About 423 respondents were involved and the data was then processed with content analysis in which 84.4% of them are willing to protect the fireflies, 66.2% volunteered in firefly conservation program, while 40.7% of them are aware that both village development and firefly conservation are important and only 32.4% agree to pay for firefly conservation which is between USD0.23-USD6.92. Meanwhile, spider web analysis shows that locals are lacking knowledge of firefly’s ecology. Lastly, a blueprint for firefly conservation should be developed to help focus preservation in the places with the highest need to slow the rate of firefly habitat loss due to development.